2021
DOI: 10.1002/anie.202111172
|View full text |Cite
|
Sign up to set email alerts
|

Realizing Record‐High Electroluminescence Efficiency of 31.5 % for Red Thermally Activated Delayed Fluorescence Molecules

Abstract: Tailor‐made red thermally activated delayed fluorescence (TADF) molecules comprised of an electron‐withdrawing pyrazino[2,3‐f][1,10]phenanthroline‐2,3‐dicarbonitrile core and various electron‐donating triarylamines are developed. They can form intramolecular hydrogen‐bonding, which is conducive to improving emission efficiency and promoting horizontal orientation and show near infrared (NIR) emissions (692–710 nm) in neat films and red delayed fluorescence (606–630 nm) with high photoluminescence quantum yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
89
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 164 publications
(94 citation statements)
references
References 72 publications
0
89
0
1
Order By: Relevance
“…To surpass the EQE over 30 % by considering molecular orientation, in 2021, Tang et al reported a series of cyano-fused pyrazinophenanthroline acceptor-based four emitters, DCPPr-α-NDPA, DCPPr-β-NDPA, DCPPr-TPA, and DCPPr-DBPPA were designed and synthesized. [34] The PL emissions in toluene solvents were around 598-620 nm, and the ~EST of emitters were maintained below 0.08 eV. On the other hand, the PLQY of all four emitters was enhanced by over 72 %.…”
Section: Chemistry-a European Journalmentioning
confidence: 93%
“…To surpass the EQE over 30 % by considering molecular orientation, in 2021, Tang et al reported a series of cyano-fused pyrazinophenanthroline acceptor-based four emitters, DCPPr-α-NDPA, DCPPr-β-NDPA, DCPPr-TPA, and DCPPr-DBPPA were designed and synthesized. [34] The PL emissions in toluene solvents were around 598-620 nm, and the ~EST of emitters were maintained below 0.08 eV. On the other hand, the PLQY of all four emitters was enhanced by over 72 %.…”
Section: Chemistry-a European Journalmentioning
confidence: 93%
“…This is in favor of balanced charge fluxes and broader recombination zones within the series of EMLs, effectively reducing triplet–triplet annihilation (TTA) processes, which are considered responsible for emitting state quenching, leading to unwanted EL efficiency roll-off [ 26 ]. These procedures ensure all these devices achieve, in general, high efficiency levels for deep-red and NIR emission OLEDs [ 2 , 8 , 19 ], especially under the practical luminance range of 100–1000 nit.…”
Section: Resultsmentioning
confidence: 99%
“…Organic near-infrared (NIR) materials and their light-emitting devices were developed rapidly since they are widely used in information-secured displays and night-vision/photodynamic therapy/signal processing devices [ 1 , 2 , 3 ]. Among them, thermally activated delayed fluorescence (TADF) organics [ 2 ] and phosphorescent transition-metal complexes based on the platinum (II) and osmium (II) family [ 3 ] seem to be ideal candidates for efficient NIR organic light-emitting diodes (OLEDs) due to both 25% singlet and 75% triplet excited states being converted into light emissions, which can generally achieve external quantum efficiencies (EQEs) of over 10%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26–30 Therefore, OLEDs based on low cost TADF materials can realize high electroluminescence (EL) efficiencies, comparable to those based on noble metal-containing phosphorescence materials. 31–36 However, many TADF materials suffer from serious concentration quenching and exciton annihilation because of the long lifetimes of the triplet excited states. 37–40 Although this situation can be addressed to some extent by employing a blend film containing the host and the dopant as an emitting layer (EML) to reduce concentration quenching, the doped devices still encounter drastic efficiency roll-offs at high voltages, which becomes a troublesome obstacle for the commercial application of TADF materials.…”
Section: Introductionmentioning
confidence: 99%